Revolutionizing polymethyl methacrylate toughness: Achieving 190% improvement with nanocellulose reinforcement while maintaining optical clarity - Liu, Guan-Ting; Shi, Shih-Chen; Rahmadiawan, Dieter (Jurnal Pendidikan Teknologi Kejuruan, 2024)
Polymethyl methacrylate (PMMA) is widely used in applications requiring high transparency and durability, such as optical lenses and protective coatings. However, its inherent brittleness limits its application in high-impact environments. This study investigates the incorporation of cellulose nanocrystals (CNCs) into PMMA to significantly enhance its toughness without compromising its optical clarity. By reinforcing PMMA with CNCs, the nanocomposites exhibited a remarkable 190% increase in toughness while maintaining 90% optical transparency. The innovation lies in achieving a balance between toughness and transparency through controlled CNC dispersion within the PMMA matrix, which minimizes excessive bonding that could lead to brittleness. Proper CNC dispersion was achieved through in-situ polymerization, allowing the nanocrystals to interact with the polymer matrix through van der Waals forces rather than covalent bonds. This approach reduces stress concentration and mitigates the formation of defects in the polymer matrix, ultimately leading to a tougher, more flexible material. In addition to enhancing mechanical properties, this study underscores the importance of controlling CNC content to preserve the intrinsic optical transparency of PMMA. These findings open new possibilities for CNC-reinforced PMMA in advanced applications that demand high mechanical performance coupled with excellent optical properties, extending its use in fields such as medical devices, protective coatings, and transparent structural materials.